2017 IEEE Symposium on Computers and Communications (ISCC) 2017
DOI: 10.1109/iscc.2017.8024579
|View full text |Cite
|
Sign up to set email alerts
|

Mm-Wave STSK-aided Single Carrier block transmission for broadband networking

Abstract: Abstract-Millimeter wave (mm-Wave) communications has been considered as a strong candidate for future wireless standards, due to the large available bandwidth in the order of gigahertz. As a result, a plethora of future services and application-oriented scenarios can be conceived, under suitable propagation conditions. Accurate physical (PHY) layer design plays a vital role in the deployment of robust transmission systems able to efficiently exploit the large bandwidth portions available in the mm-Wave freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…For instance, SM is capable of reducing the number of required RF chains and the detection complexity. Due to the aforementioned merits, preliminary work has been conducted to adopt the IM technique in mmWave transmissions [14], [15], massive MIMO [16], [17], and network coding [18]. It is believed that the IM technique can be incorporated with different critical technologies in 5G networks, where further research is needed.…”
Section: G Applications To Mobile Communicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, SM is capable of reducing the number of required RF chains and the detection complexity. Due to the aforementioned merits, preliminary work has been conducted to adopt the IM technique in mmWave transmissions [14], [15], massive MIMO [16], [17], and network coding [18]. It is believed that the IM technique can be incorporated with different critical technologies in 5G networks, where further research is needed.…”
Section: G Applications To Mobile Communicationsmentioning
confidence: 99%
“…Besides, due to the flexible structure of IM-aided frame, considerable diversity gains can be achieved from the activated pattern of the indexed entities, types of the constellation alphabets, or the selection of channel states, etc., which contributes to significant performance gain over the non-index-modulated counterparts. Therefore, IM has been applied in various formats to diverse wireless communication applications, including millimeter-wave (mmWave) transmission [14], [15], massive MIMO [16], [17] and network coding [18]. Existing IM schemes can be classified into various signal domain IM schemes, which include frequency-domain IM (FD-IM), spatial-domain IM (SD-IM) and time-domain IM (TD-IM), as well as the channel-domain IM (CD-IM) scheme.…”
mentioning
confidence: 99%
“…3 IM carries the information over some building blocks or resources. These building blocks or resources can be sub-carriers, 3 transmit antenna indexes, 4 space-time matrix, 5 pilot positions, [6][7][8] reconfigurable antennas, 9 spreading codes, 10 massive multiple-input multiple-output (MIMO), 11 indices of activated time slots, 12 relays, 13 molecular communication, 14 millimeter-wave (mmWave) transmission, 15 light-emitting diodes (LEDs), 16 orthogonal IQ components, 17 and so on. The work in Reference 18, and references therein, is an overview of IM for interested, and it is shown that IM based methods are a promising technique for future generation wireless communication technologies such as six generation (6G).…”
Section: Introductionmentioning
confidence: 99%
“…IM method allows transmitting additional bits with respect to conventional modulation schemes by mapping data bits to the indexes of different media. For example, in IM-based works, additional bits are carried by sub-carriers [17], transmit antenna indexes [18], orthogonal IQ components [19], reconfigurable antennas [20], different distinguishable constellations [21], pilot positions schemes [22][23][24], indices of activated time slots [25], molecular communication [26], massive MIMO [27], millimeter-wave (mmWave) transmission [28] etc. For more details on this important field, the reader is referred to a survey of IM schemes in [29].…”
Section: Introductionmentioning
confidence: 99%